Substance use and family violence - Campe, Margaret; Harp, Kathi; Oser, Carrie editor (San Diego : c, 2023)
The text focuses on four main domains in which substance use and violence affect families: substance use and interpersonal violence, substance use and intimate partner violence, substance use and child neglect and abuse, and substance use and elder neglect and abuse. Providing both historical context and contemporary evidence, the volume uses peer-reviewed literature, theories, and interdisciplinary perspectives to provide a comprehensive understanding of the scope of each problem, who it impacts, and effective strategies for both preventing violent behavior and intervening to stop its spread
(3ebQQGJ OQGSjI dWdGH GdLGeYI (B2024.s
Includes bibliographical references and index.
Keywords: Family violence; Drug abuse